Geometry of an Isolated Dimer of Imidazole Characterised by Rotational Spectroscopy and Ab Initio Calculations. Issue 8 (25th February 2016) - Mullaney, John C.; Zaleski, Daniel P.; Tew, David P.; Walker, Nicholas R.; Legon, Anthony C.
Abstract: An isolated, gas‐phase dimer of imidazole is generated through laser vaporisation of a solid rod containing a 1:1 mixture of imidazole and copper in the presence of an argon buffer gas undergoing supersonic expansion. The complex is characterised through broadband rotational spectroscopy and is shown to have a twisted, hydrogen‐bonded geometry. Calculations at the CCSD(T)(F12*)/cc‐pVDZ‐F12 level of theory confirm this to be the lowest‐energy conformer of the imidazole dimer. The distance between the respective centres of mass of the imidazole monomer subunits is determined to be 5.2751(1) Å, and the twist angle γ describing rotation of one monomer with respect to the other about a line connecting the centres of mass of the monomers is determined to be 87.9(4)°. Four out of six intermolecular parameters in the model geometry are precisely determined from the experimental rotational constants and are consistent with results calculated ab initio. Abstract : Do the twist : An isolated, gas‐phase imidazole dimer is generated by laser vaporisation of imidazole/copper (1/1) in the presence of an argon buffer gas undergoing supersonic expansion. Rotational spectroscopy shows that it has a twisted, hydrogen‐bonded geometry (see figure), and ab initio calculations confirm it to be the lowest‐energy conformer of the imidazole dimer.